Budget Based Education Financing Management - Jajang Suherman; Ayi Najmul Hidayat; N. Dede Khoeriah; Husen Saeful Insan (Journal of Islamicate Studies, 2022)
One important element in the quality of education is funding. Financing is sometimes also the core of every educational problem, especially if it is related to the financing of education at private universities which are mostly sourced from public funds, even though there is actually assistance from the government but it is not too significant to be used as a reference in determining policy, then the quality of private higher education of course very dependent on the management of financing management. Good financing management is one of the keys to the success of a university to advance or improve its quality. Indonesian College of Logistics Management, Pos Indonesia Polytechnic and Ma'soem University in implementing budget-based education financing management with the aim of trying to achieve productivity in education, where productivity is assessed from the economic value of each existing activity, to achieve maximum results by using costs. as minimal as possible, in order to achieve effective and efficient use of education costs.